Abelhas campeiras de Apis mellifera L. africanizada (Hymenoptera: Apidae) são suscetíveis aos óleos essenciais de Pitanga (Eugenia uniflora) e de Patchouli (Pogostemon cablin)? - Berté, Elizabete Artus (2022)
The Africanized bee Apis mellifera L. 1758 (Hymenoptera: Apidae) is a social insect with highlighted importance in agriculture and economy, mainly due to the pollination process, an important ecosystem service. In addition to pollination that benefits the production of different crops, bees produce honey, royal jelly, wax, propolis, pollen and apitoxin. However, in recent years, the mortality of these insects has been evident and mainly related to the use of pesticides. One of the alternatives to reduce the problems caused by these products is the use of essential oils, or botanical insecticides. However, the effects of essential oils on A. mellifera are still poorly understood. Thus, the objective was to evaluate the susceptibility of field bees of known age (marked) and unknown age (unmarked) of Africanized A. mellifera to the essential oils of pitangueira (Eugenia uniflora) and patchouli (Pogostemon cablin), both used in pest control. For this, four bioassays were prepared in the laboratory with essential oils at a concentration of 0.75%. The bioassays were: 1) Contact of A. mellifera (age known and age unknown) on a vitreous surface treated with essential oils; 2) Action of essential oils sprayed directly on A. mellifera (with known age and unknown age), 3) Action of essential oils on A. mellifera (with known age and unknown age) fed a diet containing the treatments and; 4) Analysis of flight behavior (vertical displacement) and flight resumption (free fall) of A. mellifera (with known age and unknown age). Essential oils caused a reduction in the probability of survival of A. mellifera bees, highlighting their toxicity within 12 hours. In bioassay 1) the essential oils reduced the survival probability of A. mellifera, differing from the control group bees. The E. uniflora essential oil caused a further reduction in the survival of bees of unknown age. In bioassay 2) the E. uniflora and, P. cablin essential oils also reduced the survival of A. mellifera bees, differing from the control group. In bioassay 3) The E. uniflora essential oil reduced the probability of survival of A. mellifera, with emphasis on the reduction in survival of bees of unknown age. Pogostemon cablin essential oil also reduced the survival probability of these bees. When analyzing the impact of essential oils on bees with known and unknown age, in the bioassay (3), it was found that the action of the oils was different between the different ages; however, differing from the survival of the control group. The essential oils of E. uniflora and P. cablin in bioassay 4, affected the flight behavior (vertical displacement) and flight resumption (free fall) of these bees. Africanized A. mellifera bees are susceptible to E. uniflora and P. cablin essential oils regardless of age and method they were exposed to the respective essential oils.